Ethic Education in Figurative Languages in The Brothers Grimm’s Fairytale the Enchanted Fish - Sulviana Sulviana; Aulia Rinjani Putri Sulya (Edumaspul: Jurnal Pendidikan, 2023)
Figurative language is a form of expression used to convey meaning. This figurative language is, often used by comparing or identifying one thing with another that has a meaning. People use figurative language to make the phrases or sentences more meaningful. The students can learn figurative language from short stories and learn the ethics of the short story. The objectives of this study were to analyze the type of figurative languages used in the short story “The Enchanted Fish” by the Brothers Grimm. This study applied qualitative descriptive approach and used content analysis to analyze the data. The writer acted as the main instrument to analyze the found figurative language. Moreover checklist was also used to support the data collection. The data was analyzed through three stages; 1). Data reduction, 2). Data representation, 3). Conclusion. The result of the study showed there were 5 sentences that containing figurative language in “the enchanted fish” by the brothers Grimm. They were pathetic fallacy and foreshadowing. Mostly of the figurative language found in the short story “the Enchanted Fish” talked about ethic education in facing challenge in life. Therefore, it is concluded that this short story is a way of teaching young people such elementary school students the ethic education in managing ethic education to children.